Таня Гроттер и посох волхвов: [повесть] / Дмитрий Емец - Емец Дмитрий Александрович (Таня Гроттер, 2004)
Экземпляры: ф.17 (20160210) / Инвентарный номер: 51161 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Е 60 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6